Guanine-Decorated Graphene Nanostructures for Sensitive Monitoring of Neuron-Specific Enolase Based on an Enzyme-Free Electrocatalytic Reaction - LI, Guang-Zhou; TIAN, Feng (Analytical Sciences, 2013)
A new and enzyme-free electrochemical immunoassay protocol was developed for the sensitive electronic monitoring of neuron-specific enolase (NSE) on a monoclonal mouse anti-human NSE antibody (mAb)-modified glassy carbon electrode, using guanine-decorated graphene nanostructures (GGN) as nanotags. To construct such an enzyme-free immunoassay format, guanine and polyclonal rabbit anti-human NSE antibody (pAb) were co-immobilized on the graphene nanostructures through the carbodiimide coupling. Based on a sandwich-type immunoassay mode, the assay was carried out in 0.1 M pH 7.4 PBS containing 5 μM Ru(bpy)32+ through the catalytic oxidation of Ru(bpy)32+ toward the guanine on the GGN. The presence of graphene nanostructures increased the immobilized amount of guanine, thus amplifying a detectable electronic signal. The covalent conjugation of guanine and pAb on the GGN resulted in a good repeatability and intermediate reproducibility down to 9.5%. Under optimal conditions, the dynamic concentration range of the developed immunoassay spanned from 0.005 to 80 ng mL−1 NSE with a detection limit of 1.0 pg mL−1 at the 3Sblank level. In addition, the methodology was evaluated by assaying the spiking serum samples, and the relative standard deviation (RSD) between the electrochemical immunoassay and a commercialized enzyme-linked immunosorbent assay (ELISA) were 2.8 – 7.0%.